Investigation on low-cost friction-based isolation systems for masonry building structures: Experimental and numerical studies. (15th September 2021) - Zhang, Chunwei; Ali, Amir; Sun, Li
Highlights: A low-cost friction-based base isolation system was studied experimentally and numerically. The dynamic behavior of isolation layer materials was tested using cyclic loading tests. Vertical rebars were used to ensure the re-centering mechanism of the isolation system. Using the proposed isolator, a considerable reduction was observed in the response of a structure. The proposed isolation system can be used for a variety of ground motions. Abstract: Masonry structures do not exhibit adequate seismic performance but they are still the most commonly constructed buildings across the globe. To enhance their seismic capacity and to protect them from the damaging effects of earthquakes in seismic active regions, an innovative low-cost friction-based seismic isolation system is developed in this study. The proposed isolation system, installed between the foundation and superstructure is made up of a 50 mm thick isolation layer material having low lateral stiffness, which is sandwiched between two 4 mm thick Teflon sheets and is further reinforced by vertical rebars. To establish the mechanical properties of the isolation system, experimental trials were performed using weak mortar, asphalt cushion, steel balls enclosed in mortar, coarse sand mortar, and rubberized mortar as an isolation layer material, and the proposed isolation system is installed between two hollow concrete blocks for testing purpose. Cyclic load tests were performed on the specimens and force-deformation curves were achieved. Two numerical models, one with a fixed base and another with the proposed isolator were developed using finite element analysis approach and analyzed against five different ground motions input. The isolation layer material used in the numerical model was selected based on friction coefficient and cyclic loading tests. In case of low seismic excitation, the isolation system does not activate to ensure structural integrity, however, when the lateral forces exceed the permissible limit then the isolation system permit deformation in both horizontal directions to dissipate seismic energy through friction while the vertical reinforcement ensure the re-centering mechanism of the structure. It is observed that the proposed isolation system considerably reduces the transmission of earthquake energy to the superstructure over a variety of ground motions. Depending upon the type of ground motion, an overall 45% − 56% reduction was observed in the absolute acceleration response of the top roof level of the isolated structure.